Parallel Optical Control of Spatiotemporal Neuronal Spike Activity Using High-Speed Digital Light Processing - Jerome, Jason; Foehring, Robert C.; Armstrong, William E.; Spain, William; Heck, Detlef H. (Frontiers in Systems Neuroscience, 2011)
Neurons in the mammalian neocortex receive inputs from and communicate back to thousands of other neurons, creating complex spatiotemporal activity patterns. The experimental investigation of these parallel dynamic interactions has been limited due to the technical challenges of monitoring or manipulating neuronal activity at that level of complexity. Here we describe a new massively parallel photostimulation system that can be used to control action potential firing in in vitro brain slices with high spatial and temporal resolution while performing extracellular or intracellular electrophysiological measurements. The system uses Digital-Light-Processing (DLP) technology to generate 2-dimensional (2D) stimulus patterns with >780,000 independently controlled photostimulation sites that operate at high spatial (5.4 µm) and temporal (>13kHz) resolution. Light is projected through the quartz-glass bottom of the perfusion chamber providing access to a large area (2.76 x 2.07 mm2) of the slice preparation. This system has the unique capability to induce temporally precise action potential firing in large groups of neurons distributed over a wide area covering several cortical columns. Parallel photostimulation opens up new opportunities for the in vitro experimental investigation of spatiotemporal neuronal interactions at a broad range of anatomical scales.